Density equalizing mapping of the global tuberculosis research architecture. Issue 4 (July 2015) - Groneberg, David A.; Weber, Esther; Gerber, Alexander; Fischer, Axel; Klingelhoefer, Doris; Brueggmann, Doerthe
Summary Background Tuberculosis belongs to the lung infectious diseases with the highest impact on global burden of disease. Yet there is no concise scientometric study about tuberculosis research. Therefore, the NewQiS project elected this subject as focus of an in depth analysis to perform density equalizing mapping in combination with scientometrics. Method In this retrospective study all publications related to tuberculosis research listed in the Web of Science database between 1900 and 2012 were identified, analyzed and submitted to density equalizing mapping procedures. Results In total 58, 319 entries on TBC were identified with the USA being the most productive country with 11, 788 publications, followed by the United Kingdom (4202), India (3456), France (2541), South Africa (1840), Germany (1747) and China (1427). Concerning the citations rate Denmark leads with 43.7 citations per article, followed by Latvia (39.1), Gambia (38.3), Senegal (34.9), and the Netherlands (31.4). Chart techniques demonstrates a widely ramified international network with a focus the joint work of USA, the UK and South Africa. Conclusions This is the first density equalizing and scientometric study that addresses tuberculosis research over a period of 112 years. It illustrates global tuberculosis research architecture and stresses the need for strengthening global research efforts and funding program.